2013 European Control Conference (ECC) 2013
DOI: 10.23919/ecc.2013.6669564
|View full text |Cite
|
Sign up to set email alerts
|

Rigid body motion tracking without linear and angular velocity feedback using dual quaternions

Abstract: This paper takes advantage of a new, recently proposed representation of the combined translational and rotational dynamic equations of motion of a rigid body in terms of dual quaternions. We show that combined position and attitude tracking controllers based on dual quaternions can be developed with relatively low effort from existing attitude-only tracking controllers based on quaternions. We show this by developing an almost globally asymptotically stable nonlinear controller capable of simultaneously follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Note that the rotational and translational kinematic equations written in terms of dual quaternions [7].…”
Section: Dual Quaternionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the rotational and translational kinematic equations written in terms of dual quaternions [7].…”
Section: Dual Quaternionsmentioning
confidence: 99%
“…As a consequence, the associated computational complexity for implementation is reduced. Moreover, the state estimate of the DQ-MEKF can be directly used by the pose controllers given in [7,8] without additional conversions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the spacecraft pose control systems, several algorithms with dual quaternion representation are appeared in [3,4,12]. All of them take the advantage of the dual quaternion algebra and succeed in stabilizing the system for both rotational and translational motions simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the unit dual quaternion is the most compact and computationally efficient tool among others [1,5,6]. Due to such efficiency of the unit dual quaternion in 6-DOF rigid body dynamics, it is recently adopted to the controller design problems in [3,4,7,9,12,14,15] to name a few.…”
Section: Introductionmentioning
confidence: 99%